The Euroflow PID Orientation Tube in the diagnostic workup of primary immunodeficiency: Daily practice performance in a tertiary university hospital - Neirinck, Jana; Emmaneel, Annelies; Buysse, Malicorne; Philippé, Jan; Van Gassen, Sofie; Saeys, Yvan; Bossuyt, Xavier; De Buyser, Stefanie; Burg, Mirjam van der; Pérez-Andrés, Martín; Orfao, Alberto; van Dongen, Jacques J. M.; et al. (Frontiers in Immunology, 2022)
Multiparameter flow cytometry (FCM) immunophenotyping is an important tool in the diagnostic screening and classification of primary immunodeficiencies (PID). The EuroFlow Consortium recently developed PID Orientation Tube (PIDOT) as a universal screening tool to identify lymphoid-PID in suspicious patients. Although PIDOT can identify different lymphoid-PIDs with high sensitivity, clinical validation in a broad spectrum of patients with suspicion of PID is missing. In this study, we investigated the diagnostic performance of PIDOT, as part of the EuroFlow diagnostic screening algorithm for lymphoid-PID, in a daily practice at a tertiary reference center for PID. PIDOT was tested in 887 consecutive patients suspicious of PID at the Ghent University Hospital, Belgium. Patients were classified into distinct subgroups of lymphoid-PID vs. non-PID disease controls (non-PID DCs), according to the IUIS and ESID criteria. For the clinical validation of PIDOT, comprehensive characterization of the lymphoid defects was performed, together with the identification of the most discriminative cell subsets to distinguish lymphoid-PID from non-PID DCs. Next, a decision-tree algorithm was designed to guide subsequent FCM analyses. The mean number of lymphoid defects detected by PIDOT in blood was 2.87 times higher in lymphoid-PID patients vs. non-PID DCs (p<0.001), resulting in an overall sensitivity and specificity of 87% and 62% to detect Severe Combined Immunodeficiency (SCID), Combined Immunodeficiency with associated or syndromic features (CID), Immune Dysregulation disorder (ID) and Common Variable Immunodeficiency (CVID). The most discriminative populations were total memory and switched memory B-cells, total T-cells, TCD4+cells and naive TCD4+cells, together with serum immunoglobulin levels. Based on these findings, a decision-tree was designed to guide further FCM analyses, which resulted in an overall sensitivity and specificity for all lymphoid-PID of 86% and 82%, respectively. Altogether, our findings confirm that PIDOT is a powerful tool for the diagnostic screening of lymphoid-PID, particularly to discriminate patients with (S)CID, ID and CVID from other patients suspicious of PID. The combination of PIDOT and serum immunoglobulin levels, provides an efficient guide for further immunophenotypic FCM analyses, complementary to functional, and genetic assays, for accurate PID diagnostics.